2018
DOI: 10.31227/osf.io/sxhp8
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Belajar Memahami Bahasa Generasi Milenial

Abstract: Bahasa Indonesia dan Media SosialTidak dapat dimungkiri, perkembangan media sosial dewasa ini turut berpengaruh terhadap perkembangan bahasa Indonesia. Bahasa Indonesia yang berkedudukan sebagai bahasa nasional digunakan sebagai alat pengembangan kebudayaan nasional, ilmu pengetahuan dan teknologi. Kebudayaan nasional yang beragam, rasanya sulit disebarluaskan kepada seluruh masyarakat yang juga beragam bahasa daerah dengan menggunakan bahasa selain bahasa Indonesia. Hal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 0 publications
1
5
0
5
Order By: Relevance
“…This attitude of understanding language norms carefully uses linguistic norms and is polite in its use. The results of the above research are in line with the research by Mansyur (2018). According to him, positive language attitudes in higher education are not fully positive for some students.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This attitude of understanding language norms carefully uses linguistic norms and is polite in its use. The results of the above research are in line with the research by Mansyur (2018). According to him, positive language attitudes in higher education are not fully positive for some students.…”
Section: Discussionsupporting
confidence: 82%
“…The characteristics of a positive attitude towards a language include (1) language loyalty which encourages people who have the language to maintain their language and, if necessary, prevent other languages' influences, (2) language pride which encourages people who have the language to develop their language and use it as a symbol of identity and community unity, (3) awareness of the norm which encourages people to use their language carefully and politely; and it is a factor that has a tremendous influence on actions, namely the activity of using language. Mansyur (2018), in his study, found that positive language attitudes in higher education are not entirely positive for some students. This is because students tend to be more confident when they use foreign languages.…”
Section: Introductionmentioning
confidence: 90%
“…Tentang Kota Makassar, penelitian Syahruddin Mansyur (2002) berhasil mengungkap pertumbuhan Kota Makassar pada Akhir Abad XVII hingga Awal abad XX yang dibaginya menjadi tiga fase. Pertumbuhan keruangan Kota Makassar masa Kolonial tersebut sangat dipengaruhi oleh situasi politik, keamanan dan kehidupan sosial masyarakat (Mansyur, 2002). Penelitian Irfan Mahmud (2003) tentang Struktur Kota Palopo Abad XVII -XIX juga berhasil menjelaskan bahwa sejak masa pendudukan Belanda pada tahun 1920, terjadi pertumbuhan struktur kota secara signifikan dengan dibangunnya pasar dan rumah jabatan pada alun-alun istana kerajaan.…”
Section: Pendahuluanunclassified
“…They coined the term when children born in 1982 entered preschool, and the media at the time began to refer to it as a group connected to the new millennium upon graduating high school in 2000. The two wrote about this group in the book Generations: The History of America's Future Generations and Millennials Rising: The Next Great Generation (Mansyur, 2018).…”
Section: Introductionmentioning
confidence: 99%